Qualidade da água na carcinicultura na Grande Aracaju - Sergipe, Brasil. - Santos, Gracylenne Prata (2009)
Known to be essential for human survival, water is one of the most important natural resources of the planet; its quality is of fundamental importance for the sustainability of any agroecosystem. There is a worldwide trend in its preservation, to ensure its availability for various purposes. The aquaculture activity in the cultivation of shrimp has as one of its main problems the disposal of its effluents in aquatic ecosystems. This work aims to analyze, through physico-chemical parameters, the quality of water used in shrimp cultivation in Great Aracaju, in the county of Nossa Senhora do Socorro, SE. The water parameters were measured: pH, temperature, turbidity, suspended solids, total dissolved solids, dissolved oxygen, electrical conductivity, total phosphorus, sulfate, total nitrogen, ammonia, nitrate, nitrite, chlorophyll A, alkalinity, biological and chemical demand of oxygen, total organic carbon and salinity, in three sampling campaigns: October and December, 2008 and January, 2009. Samples were collected at three stations: two nurseries and one spillway. The analyses were conducted in the Laboratório de Química Analítica Ambiental (Laboratory of Environmental Analytical Chemistry) in accordance with Standard Methods. The total phosphorus (nursery: 38.9 mg/L; spillway: 4.3 mg/L), total nitrogen (nursery: 70.3 mg/L; spillway: 60.4 mg/L), total organic carbon (nursery: 19.6 mg / L; spillway: 14.6 mg / L), biological oxygen demand (nursery: 75.8 mg / L; spillway: 66.7 mg / L), dissolved oxygen (nursery: 70.3 mg/L; spillway: 60.4 mg / L) exceeded the limit allowed by Brazilian legislation (CONAMA Resolution 357/2005 and 20/1986) (total P = 0.124 mg / L, total N = 0.40 mg / L,COD <3mg / L, DBO <5mg / L) for brackish water class l. The levels of chemical oxygen demand (nursery: 64.2mg/L; spillway: 80.0 mg/L) were higher than those reported in other studies. The accumulation of nutrients found may be related to the form of management; supplies used such as feed, fertilizers and antibiotics, accumulated organic matter (feed not consumed, excreta); density of shrimp in ponds, the concentration of this nutrient in the composition of the feed used and the utilization of the area as a disposal of domestic sewage in natura.